Comprehensive study of the volatile profile of Niágara Rosada (Vitis labrusca) wines produced from Brettanomyces anomalus using GC–FID–MS: a chemical and sensory approach - dos Santos Júnior, Jorge Roberto [UNESP]; dos Santos, Ingrid Duarte; Klein, Bruna; Wagner, Roger; de Castilhos, Maurício Bonatto Machado; Del Bianchi, Vanildo Luiz [UNESP] (Springer Nature, 2023)
There has been a controversy concerning the use of Brettanomyces in wines due to its questionable behavior. Some authors reported that this yeast causes adverse effects in wines; other authors reported that this yeast could promote a floral and fruity aroma for wines. In this context, this study analyzed Brettanomyces anomalus as alternative yeast for winemaking, providing the relationship between chemical and sensory approaches. Isoamyl acetate (159 μgL−1), linalyl acetate (20.6 μgL−1), ethyl butanoate (176 μgL−1), ethyl hexanoate (29.2 μgL−1), and ethyl octanoate (6.30 μgL−1) were related to flavor acceptance, providing a sweet, fruity, and floral profile for the wines. Terpenes (β-myrcene, 20.7 mgL−1, and levomenol, 10.3 μgL−1) and acids, synergistically, drove the aroma and body acceptance. The overall acceptance was related to carbonilic compounds (nonanal) giving a citrus/green scent and benzene compounds, the latter contributing synergistically. This study showed the relevance of the use of Brettanomyces to improve the Vitis labrusca wine quality, resulting in sweet, fruity, and floral aroma, features very appreciated by Brazilian consumers.
Keywords: Brettanomyces; Niágara Rosada; Non-Vitis vinifera; Sensory acceptance; Volatile compounds; Wine